2019
DOI: 10.1039/c8mh01291a
|View full text |Cite|
|
Sign up to set email alerts
|

Stress-localized durable icephobic surfaces

Abstract: We introduce and present the fundamentals of stress-localization concept to minimize adhesion of ice or other contaminants on a surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 42 publications
1
159
1
Order By: Relevance
“…Thus it could be concluded that when the same failure mode is prevailed, no loading mode dependency, or roughness dependency may be anticipated. However, this observation/conclusion should be further examined with polymer-based interfaces that might stimulate stress localization at the interface with inhomogeneous stress distribution at the submicron level [29]. A set of direct shear samples ranging with b=5-57 mm and push-out samples with b= 5-8 mm, were tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it could be concluded that when the same failure mode is prevailed, no loading mode dependency, or roughness dependency may be anticipated. However, this observation/conclusion should be further examined with polymer-based interfaces that might stimulate stress localization at the interface with inhomogeneous stress distribution at the submicron level [29]. A set of direct shear samples ranging with b=5-57 mm and push-out samples with b= 5-8 mm, were tested.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the dependency on the mode of interface loading is also critical, as tensile and shear strengths of the interface were reported to be different [12]. Moreover, the utilization of elastomeric icephobic surfaces has exposed the role of interfacial cavitation to reduce the shear strength of ice adhesion [27][28][29]. Cavitation is a primarily tension driven phenomenon [30]; thus, it is important to quantify the difference if any, between shear and tensile adhesion of the icesolid interface.…”
Section: Fig 1 Summary Of Reported Ice Adhesion Strength For An Ice/mentioning
confidence: 99%
“…Surfaces with ice adhesion strength below 10 kPa are often denoted as super-low, or ultra-low, ice adhesion surfaces (SLIAS) [6]. In the past years, examples of surfaces reaching below 1 kPa have also been reported [12][13][14]. However, the field of low ice adhesion materials research has been known to operate by continuum theory or a trial-and-error strategy, where the focus has been on developing new surfaces and coatings without fully understanding the underlying mechanisms [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…of surfaces that can facilitate crack generation through stiffness inhomogeneity and deformation incompatibility as well as achieve super-low ice adhesion strength without the use of any surface additives. 18,19 Such MACI surfaces can be combined with other mechanisms to further reduce ice adhesion. Notably, other new strategies for anti-icing have emerged, particularly those that involve ice growth and patterns into the design of surface icephobicity.…”
Section: New Conceptsmentioning
confidence: 99%
“…For the sake of mechanical robustness, PDMS with the same silicone base as that of silicon rubber was made for LLG 2, as it is one of the most common options for fabricating icephobic coatings. [17][18][19][40][41][42] In particular, silicon wafers with pillars were used as templates for molding PDMS; an example is shown in Fig. S8 (ESI †).…”
Section: Design Principles and Fabrication Of Icephobic Llgsmentioning
confidence: 99%